Economies of Scale and Efficiency in the Wastewater Treatment Sector: A Decision Tree Approach - Vicent Hernández-Chover; Águeda Bellver-Domingo; Lledó Castellet-Viciano; Francesc Hernández-Sancho (Applied Sciences)
In this study, we use the efficiency analysis trees (EAT) model to evaluate the efficiency of wastewater treatment plants (WWTPs), focusing on identifying the key variables that enhance their performance. While traditional methods consider factors such as the plant size, age, and technology, the EAT model improves the precision of and reduces errors in the efficiency estimation process. The results highlight the significance of facility size, particularly in areas with smaller populations, suggesting that economies of scale can play a crucial role in optimizing treatment processes. Centralizing the sector could lead to cost savings through ensuring better resource allocation and more effective management strategies. This study provides insights into how facility dimensions impact efficiency, aiding in strategic planning for wastewater treatment operations. The novelty of this study pertains to its implementation of the EAT model to assess efficiency from an economic point of view. Specifically, this makes it possible to identify which facility dimensions ensure better performance and, consequently, will help operators to establish criteria for intervention and geographical planning, both technically and economically.